The Influence of Basic Disaster Management Training on Competencies in The Human Resources Development Agency of North Sumatra Province - Yurlinda, Yurlinda; Isa Indrawan, Muhammad (PT. Multidisciplinary Press Indonesia, 2024)
The aim of this research is to determine and analyze the influence of Basic Training on Employee Competency of North Sumatra Human Resources Development Agency employees. This research was carried out at the North Sumatra Human Resources Development Agency. The type of research is associative quantitative. The sample in this study was 107 employees of the North Sumatra Human Resources Development Agency. The sampling technique in this research uses saturated samples so that the entire population will be a sample of 107 people. The research results show that Basic Training has a positive but not significant influence on Employee Competency as indicated by the T-Statistic value of 2.784 > 1.659 and the P Value of 0.000 < 0.05. This shows that improvements in Basic Training will be able to increase the Competency of Employees of the North Sumatra Human Resources Development Agency. The adjusted R Square value is 0.214 or 21.40%, which means that basic training has a low influence on employee competency, while the remaining 78.60% is influenced by other factors that have not been studied.